Knowledge, innovation and internationalization : essays in honour of Cesare Imbriani - Imbriani, Cesare; Morone, Piergiuseppe (Routledge, 2012)
As firms increasingly rely on knowledge as a key factor for innovation, the ability to innovate is increasingly perceived as a key asset for being competitive in international markets. This new volume argues that innovation, knowledge and internationalisation should be viewed as tightly related concepts. It provides a stimulating and comprehensive framework for understanding key tendencies in modern economics, as well as an overview of the state of the art in the three fields covered. The first section explores in detail the relationship between knowledge and the innovative capabilit.